Phase diagram of magnetostrictive Fe-Ga alloys: insights from theory and experiment. (1st February 2019) - Matyunina, M. V.; Zagrebin, M. A.; Sokolovskiy, V. V.; Pavlukhina, O. O.; Buchelnikov, V. D.; Balagurov, A. M.; Golovin, I. S.
ABSTRACT: The structural, electronic and magnetic properties of Fe 100 − x Ga x alloys are studied computationally in the composition range up tox ≤ 31.25 at.% and experimentally about 27 at.%. Ga content. Using ab initio calculations, it is shown that as Ga content increases, the lattice parameters are found to increase for all types of structures, as opposed to the magnetic moment behavior. The phase diagram is plotted as a function of energy. In agreement with experimental results, the following sequences of phase transformations are observed: D03 →A2 (6.25 ≤ x ≤ 18.75 at.%), D0 3 → L1 2 → A2 (18.75 < x ≤ 21.875 at.%), and L1 2 → D0 19 → B2→ A2 (21.875 < x ≤ 31.25 at.%). It is found that the L12 cubic structure possesses the largest degree of spin polarization. Experimental studies of Fe-Ga as cast alloys at a constant heating rate and isothermal annealing carried out by means of in situ neutron diffraction and vibrating sample magnetometry demonstrate the sequence of phase transitions of the I and II order.